Changes in type since 1960 - Good, D. (Kansas Agricultural Experiment Station, 2011)
America owes a great deal of the founders of the Hereford, Angus and Shorthorn breeds of beef cattle, the dominant U.S. beef breeds. Early Scotch and English breeders in developing the beef breeds aimed to breed cattle with superior beef quality. This, by necessity, had to be done under, in many instances, vigorous environmental conditions.
Keywords: Beef; Purebred bulls; Quality; Breeds